Comparison of Composting Method using Black Slodier Fly Larvae and Takakura Method on Compost Quality and Quantity - Aziz, Rizki; Ruslinda, Yenni; Pratiwi, Hesti Anggia; Rahmi, Jumita; Jonrinaldi, Jonrinaldi (CIVED, 2024)
Organic waste needs to be processed so as not to pollute the environment. Processing of organic waste can be done through composting. This study aims to see the effect of composting method using BSF larvae and composting using takakura method on the quality and quantity of compost produced. The variety of waste types in this study consisted of variations A (65% vegetable waste + 35% fruit waste) and B (60% vegetable waste + 40% food waste). Bioconversion using BSF larvae aged 7 days with bidaily litter as much as 0.5 kg for 14 days. The results of the analysis of the quantity, maturity, and quality of variations A1, A2, B1 and B2 meet compost standards according to SNI 19-7030-2004. The most optimal variation of the study (A2 variation). This variation produces compost for (20 days), the quality of physical and macro elements has met the quality standards of domestic waste compost and the quantity of compost produced is more than 1.10 kg.